2005
DOI: 10.1108/03074800510608675
|View full text |Cite
|
Sign up to set email alerts
|

Comparing polarized perspectives: librarians' professional skills and development

Abstract: Purpose -The main aim of the research conducted was to identify whether the particular country environment of today's professional librarian impacts upon his/her skills capabilities as well as upon his/her access to opportunities for continued development. Design/methodology/approach -Data was sourced by means of a survey administered to professional librarians mainly from the developing Caribbean Region and the developed North American countries. Firstly, the satisfaction level of librarians with regard to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Tyrell (2015) looked at the CPD activities of academic librarians at two Jamaican universities and their motivation to engage in CPD. Gosine-Boodoo and McNish (2005) compared the perspectives of librarians from developed and developing countries on their level of skills satisfactions. Gosine-Boodoo (2006) sought to present a demographic profile of special librarians in the Caribbean region based on a survey of participants at the 2004 Annual ACURIL conference.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tyrell (2015) looked at the CPD activities of academic librarians at two Jamaican universities and their motivation to engage in CPD. Gosine-Boodoo and McNish (2005) compared the perspectives of librarians from developed and developing countries on their level of skills satisfactions. Gosine-Boodoo (2006) sought to present a demographic profile of special librarians in the Caribbean region based on a survey of participants at the 2004 Annual ACURIL conference.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is noteworthy, that the literature revealed that there is a dearth of CPD research as it relates to academic librarians in Trinidad and Tobago. The studies to date are Gosine-Boodoo and McNish (2005), which examined the geo-economic position of librarians in the attainment of their professional development; and Hosein, Y. and Bowen-Chang, P. (2014, 2011) and Bowen-Chang, P. and Hosein, Y (2009) on cataloging training at the University of the West Indies, St. Augustine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corcoran (2014, p. 176) recognized that “the availability of relevant and accessible continuing professional development opportunities has never been more urgent for librarians, and the survival of the profession depends on the willingness of its members to engage with these opportunities during their working lives and to keep ahead of the curve, as technological developments continue to transform research and scholarship practices”. However, Gosine-Boodoo and McNish (2005, p. 365) cautioned that the library profession “must purposefully engage in instilling relevance into skills preparedness programs and in creating continuous development opportunities”.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Library and information science professionals have exhibited an interest in keeping up-todate in order to respond to trends in new technologies, information sourcing, and user needs (Ramaiah & Moorthy, 2002). An obvious demand for such professional training has arisen to fill the void between university pre-service education and dynamic work environments (Gosine-Boodoo & McNish, 2005).…”
Section: Introductionmentioning
confidence: 99%